Pulmonary sclerosing hemangioma: a unique epithelial neoplasm of the lung (report of 26 cases) - Chen, Bojiang (BioMed Central, 2013)
BACKGROUND: Pulmonary sclerosing hemangioma (SH) is an uncommon tumor. The aim of this study was to identify the origin of pulmonary SH and summarize its clinicopathologic features. METHODS: Data of 26 cases of pulmonary SH were collected and reviewed, including their clinical symptoms, chest radiological examinations, treatments, and pathological findings. RESULTS: Female patients of pulmonary SH were markedly frequent (n=23, 88.46%). Solitary mass or nodule in the lung fields was the most common manifestation (n=24, 92.31%), especially in the right middle lobe (n=9, 34.62%). There were two kinds of tumor cells: lining cells and round cells. All tumors contained a mixture of papillary, solid, sclerotic, and hemorrhagic patterns. Immunohistochemistry with a variable number of antibodies was performed for some cases. All of the detected specimens revealed strong reaction of lining cells with epithelial markers, such as thyroid transcription factor-1 (TTF-1), epithelial membrane antigen (EMA), cytokeratin (CK), pancytokeratin (PCK), and cytokeratin 7 (CK-7), while round cells were positive with TTF-1 and EMA. Until the end of last contact, none of the patients died or suffered from the recurrence of the disease after surgical treatment. CONCLUSIONS: Pulmonary SH is a unique neoplasm of the lung with a characteristic solitary mass or nodule. Pulmonary epithelium might be the primary origin of the tumor cells.